2018
DOI: 10.1111/febs.14429
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the nitrosuccinate lyase CreD in complex with fumarate provides insights into the catalytic mechanism for nitrous acid elimination

Abstract: Nitrosuccinate lyase CreD, EC4.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…To follow the fate of acetylhydrazine, we also reconstituted the activities of FzmN and FzmO, revealing that acetylhydrazine is first condensed onto the side chain carboxyl group of glutamic acid to form glutamylacetylhydrazine (5) before deacetylation to yield glutamylhydrazine (6). Glutamic acid is present in relatively high concentrations in the cytoplasm of most bacteria, and perhaps for that reason, glutamic acid has previously been demonstrated to be a common carrier molecule to effect many different types of transformations 18 In the fosfazinomycin biosynthetic pathway, we previously reported that argininylhydrazine is the substrate for the N-methyltransferase FzmH 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow the fate of acetylhydrazine, we also reconstituted the activities of FzmN and FzmO, revealing that acetylhydrazine is first condensed onto the side chain carboxyl group of glutamic acid to form glutamylacetylhydrazine (5) before deacetylation to yield glutamylhydrazine (6). Glutamic acid is present in relatively high concentrations in the cytoplasm of most bacteria, and perhaps for that reason, glutamic acid has previously been demonstrated to be a common carrier molecule to effect many different types of transformations 18 In the fosfazinomycin biosynthetic pathway, we previously reported that argininylhydrazine is the substrate for the N-methyltransferase FzmH 15 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during the biosynthesis of cremeomycin, a flavin-dependent monooxygenase, CreE, oxidizes aspartic acid to nitrosuccinic acid (1, Fig. 1b), and a lyase, CreD, subsequently liberates nitrous acid 6 .…”
mentioning
confidence: 99%
“…Furthermore, preliminary experiments explored the origin of the terminal N atom of the diazeniumdiolate group and chromatographic evidence suggested that it originated from nitrite. Recently, several reports have indicated similar biosynthetic pathways for the diazeniumdiolate alanosine, the diazo compounds cremeomycin and kanamycin, the pyridazine azamerone, the N ‐hydroxytriazenes triacsins and the hydrazide fosfazinomycin …”
Section: Methodsmentioning
confidence: 99%
“…An alternative mechanism for N−N bond formation features the reaction between an amine and nitrous acid that is generated through the sequential function of a flavin‐dependent enzyme (CreE) and a lyase (CreD) on aspartate (Figure S1) . The diazo moiety found in cremeomycin, for example, is generated through the reaction between an arylamine and nitrous acid promoted by an acyl‐CoA ligase homologue (CreM, Figure S1) .…”
Section: Figurementioning
confidence: 99%